Potato Cyst Nematodes: Geographical Distribution, Phylogenetic Relationships and Integrated Pest Management Outcomes in Portugal - Camacho, Maria João; de Andrade, Eugénia; Mota, Manuel; Nobrega, Filomena; Vicente, Claudia; Rusinque, Leidy; Inácio, Maria Lurdes (Frontiers in Plant Science, 2020)
The identification and phylogenetic relationships of potato cyst nematodes (PCN) were studied to assess the potential value of geographical distribution information for integrated pest management of potato production in Portugal. This research focused on PCN species, Globodera pallida and G. rostochiensis. From 2013 until 2019, 748 soil samples from the rhizosphere of different potato cultivars were surveyed in Portugal mainland, to detect and identify both species and track their location. PCN are widespread invasive species throughout Portugal. In fact, during the survey period an incidence of 22.5% was estimated for the tested samples. The patterns of infestation vary among regions, increasing from south to north, where PCN were first detected. Currently, both species are present in all potato producing regions of the country, with a greater incidence of G. pallida. Phytosanitary control measures are driving to the observed results. The use of potato cultivars resistant to G. rostochiensis led to a decrease of this species but had no influence on G. pallida detections, which continues its reproduction freely since there are no effective resistant cultivars for this species. The relationship between the presence, infestation rate, spread and geographical distribution of PCN is discussed in terms of behavioural responses of the potato cultivars and the implications for developing new integrated crop protection measures.